3D-Printing of Artificial Aortic Heart Valve Using UV-Cured Silicone: Design and Performance Analysis - Atila Ertas; Erik Farley-Talamantes; Olkan Cuvalci; Ozhan Gecgel (Bioengineering)
The advancement of medical 3D printing technology includes several enhancements, such as decreasing the length of surgical procedures and minimizing anesthesia exposure, improving preoperative planning, creating personalized replicas of tissues and bones specific to individual patients, bioprinting, and providing alternatives to human organ transplants. The range of materials accessible for 3D printing within the healthcare industry is significantly narrower when compared with conventional manufacturing techniques. Liquid silicone rubber (LSR) is characterized by its remarkable stability, outstanding biocompatibility, and significant flexibility, thus presenting substantial opportunities for manufacturers of medical devices who are engaged in 3D printing. The main objective of this study is to develop, refine, and assess a 3D printer that can employ UV-cured silicone for the fabrication of aortic heart valves. Additionally, the research aims to produce a 3D-printed silicone aortic heart valve and evaluate the feasibility of the final product. A two-level ANOVA experimental design was utilized to investigate the impacts of print speed, nozzle temperature, and layer height on the print quality of the aortic heart valve. The findings demonstrated that the 3D-printed heart valve’s UV-cured silicone functioned efficiently, achieving the target flow rates of 5 L/min and 7 L/min. Two distinct leaflet thicknesses (LT) of the heart valve, namely 0.8 mm and 1.6 mm, were also analyzed to simulate calcium deposition on the leaflets.